Pengaruh Sosialisasi Politik Partai Islam Terhadap Perilaku Pemilih Pada Pemilu 2019 di Kecamatan Undaan Kabupaten Kudus - Nur Amanah; Nevy Rusmarina Dewi (JPW (Jurnal Politik Walisongo), 2023)
Islamic political parties in Indonesia have colored the post-reform democratic party. Between parties are trying to persuade people who are predominantly Muslim to vote for them, but the phenomenon is that these parties are fighting over the masses with nationalist parties that have taken root in the hearts of the people. This paper will discuss how the political socialization of Islamic parties is carried out in the 2019 elections in Undaan Kudus District and what factors influence the low vote acquisition of Islamic parties in Undaan District. The research method in this paper uses qualitative research and is presented descriptively. The results of the research show that the Islamic Party in Undaan District has a lower vote share than the nationalist party. Islamic parties in Undaan carry out political socialization through socialization agents, namely family, social groups and mass media, namely internet social media. Apart from that, they use other methods of conveying political socialization, such as the use of political props (billboards, banners, etc.) and also Islamic parties partner with Kiai as a means of conveying political socialization. The low number of votes acquired by Islamic parties in the context of voting behavior is influenced by the tendency shown by the people of Undaan District who vote rationally are not too interested in political concepts, but more in the benefits they get.